Peran Orang Tua Terhadap Pembentukan Karakter Anak Dalam Menyikapi Bullying - Yulianti Yulianti; Muhammad Syukur (Lembaga Pengembangan Kinerja Dosen, 2023)
The problem in this study is that there are cases of bullying that occur in school students, and this is a very serious problem so it must be followed up again. So, the role of parents is very necessary in this case, and not just relying on the school. This study aims to provide an overview of the formation of parents in the process of forming children's character in responding to bullying cases. The method used in this research is descriptive research. The results of the study show that the role of parents is needed, especially in the process of forming children's character, because remembering that parents are the ones who will be used as role models by children, parents can shape character for children by setting an example, teaching good things, interact with their environment, and children's involvement in home activities. In this way the character that is instilled by parents from an early age in children will form good character such as forming children to be stronger and able to carry themselves in their environment, children will be more confident. In the case of bullying, parents are expected to educate and strengthen children to be braver and not afraid and always have self-confidence, provide the ability to defend themselves or even take revenge, select people who will be friends with them.